Development of an Innovative Mango's Wrapper Tool - Kassim, Noraniah; Kosnan, Hairizza; Salleh, Noor Iskandar; Noor, Hafsa Mohammad; Mohammad Noor, Hafsa; Noor, Hafsa Mohammad (International Journal of Integrated Engineering, 2019)
This paper presenting a new design and development of an innovative and user-friendly tool by using mechanism of compression spring to wrap mango fruits in an efficient and systematic manner. The tool is capable to solve the problem faced by mango farmers or entrepreneurs during traditionally wrapping process. Previously, the wrapping process is handled manually by using paper wrapper and rope while ladder is sometimes used for tall trees. 30 mango fruits are picked for size sampling. The diameter for the mature mango fruits is within the range of 5.8cm to 7.9cm. The suitable casing size is determined to be 10cm in which 3.1 cm is the tolerance. The tool is designed by using SolidWork 2016. Later, tool fabrication process is carried out including cutting and joining the parts such as steel compression spring, paddle , cable and PVC pipe . The analysis is focused on the compression spring and the maximum force of 45.117N is applied on the pedal to pull the jaws while releasing the rubber band. Meanwhile, the tool is highly efficient and the time for the tool to wrap one mango fruit is 65 seconds compared to 190 seconds by way of traditional method. Significant saving in term of labor workforce is as much as 67% and the ratio of manpower requirements is reduced to 3: 1. Among the factors contributing to the saving are the used of 210cm long pole which eliminate the need of use a ladder. Lastly the tool is lightweight, convenience to use with minimum maintenance.